The mediating role of workplace spirituality on the relationship of Meaning of Life and family cohesion of teachers in COVID-19 - Zaeimzadeh, Seyed Mahdi; Jafari, Asghar (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the mediating role of workplace spirituality on the relationship of Meaning of Life and family cohesion of teachers in COVID-19. Methods: Method was descriptive- correlation. Population was married woman and man teachers of elementary schools in academic year 2020-2021 in the region 18 of Tehran. According to the table of Krejcie & Morgan (1970) and using multi cluster sampling 175 participants with inclusion criteria were selected and completed the questionnaires of Samani, s (2006) family cohesion, Milliman, s workplace spirituality and Salehi, s (2005) Meaning of Life. Data were analyzed by Pearson correlation and hierarchy regression. Results: The results indicated that there is a positive and significant relationship between Meaning of Life and family cohesion of teachers in COVID-19 (p